Comprehensive Analysis of Fatal Road Accidents: Patterns and Characteristics of Injuries in a Forensic Medicine Setting - Pati, S; Mallick DK; Shukla, AK; Bisoyi, CK; Das , S; Sahoo , N (Journal of Indian Academy of Forensic Medicine, 2024)
An accident is an occurrence that takes place suddenly, unexpectedly and unintentionally, often arising from unforeseen circumstances. Road traffic injuries (RTA/RTI) resulting in death, especially Motor Vehicle Traffic Accidents (MVTA), have been recognized as a concealed epidemic with global impact, affecting every segment of society. This study has been conducted at a tertiary care hospital, aimed to identify different patterns and distributions of injuries, with the goal of devising preventive measures for the future.